What are the Driving Factors of the Landfill Disposal Rate in Italy? A Semi- Parametric Analysis for Policy Implications - Agovino, Massimiliano; Casaccia, Mariaconcetta; Ferrara, Maria; Garofalo, Antonio (Journal of Environmental Accounting and Management, 2026)
This paper aims to investigate the driving factors of the Landfill Disposal Rate (LDR) on Italian territory and attempts to provide some policy recommendation to reduce it. Hence, we implement a two-step analysis. First, we perform a cluster analysis (CA) to 103 Italian provinces on the LDR driving factors. Second, in the light of the CA results, we implement a semi-parametric estimator in order to identify two components of the LDR distribution: the effects of the coefficients and the effects of the characteristics. The paper documents a considerable heterogeneity among the 103 Italian provinces under consideration. This emphasizes that policy makers cannot consider a unique policy recommendation to reduce landfill. Rather policy interventions must be differentiate according to such a heterogeneity.